STUDY OF THE RELIABILITY OF THE EXTERNAL OVERVOLTAGE PROTECTION OF THE 7 IN 1 BUILDING AT TANJUNGPURA UNIVERSITY USING ELECTROGEOMETRY METHOD - Florus, Egi; Danial, Danial; Rajagukguk, Managam (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
The 7 In 1 Building at Tanjungpura University, located in Pontianak, along the equator, faces frequent lightning strike risks, necessitating the installation of a reliable external voltage protection system. This study aims to determine the configuration of a conventional protection system using the electrogeometry method, comparable in reliability to the Early Streamer Emission (ESE) protection system. Considering a lightning current of 16 kA and a lightning strike distance to the ground of 60,63 meters, the required number of conventional protection systems for optimal reliability is determined: the Library Building needs 104 rods, the Conference Building 62 rods, Joint Lecture Buildings A and B at Tanjungpura University 59 rods each, and the Integrated Laboratory Building 17 rods. The use of conventional voltage protection systems with the electrogeometry method has proven to achieve good reliability, equivalent to that of Early Streamer Emission (ESE), despite generating a smaller protection radius and requiring a higher number of finials.